PENGARUH PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAM ACHIEVEMENT DIVISION (STAD) DIAWALI TUGAS RUMAH MEMBUAT MIND MAP TERHADAP HASIL BELAJAR BIOLOGI SISWA KELAS XI IPA SMAN 5 PADANG - Manalu, Elvi Yuliana; Helendra, Helendra; Maizeli, Annika (STKIP PGRI Sumbar, 2013)
ABSTRACT This research motivated by the lack of students learning outcomes biology because of a lack of understanding and mastery of the subject matter on the subjects reproduction system and the student tend to be passive and less participate in the study. One of the strategies that cab be used to increase the Student Team Achievement Division (STAD) with Mind Mapping fortheir homework. This study in a experimental study with randomized research design posttest only control group design. Population in this study were all students of class XI IPA SMAN 5 Padang enrolled in the second semester of academic year 2012/2013. Sampling done in order to Purposive Sampling. As a result it was found that class XI IPA1 and IPA2 sampel. Sampel was selected by the equal of the students mean score than taken randomly with as a class experiment IPA1 and IPA2 class control. Purpose of this study was to determine the effect of the type learning strategies Student Team Achievement Division (STAD) with Mind Mapping fortheir homework on learning outcomes biology class XI IPA SMAN 5 Padang. The results showed that student classroom experiment is higher than the control class. Based on the hypothesis t-test count rates obtained (3,95) > ttabel (1,67) this means that the hypothesis is accepted. It can be concluded that the learning outcomes of students in learning biology using learning strategies type Student Team Achievement Division (STAD) with Mind Mapping fortheir homework is better than conventional learning.